2016
DOI: 10.1016/j.jaut.2016.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles and opportunities for targeting the effector T cell response in type 1 diabetes

Abstract: Autoreactive lymphocytes display a programmed set of characteristic effector functions and phenotypic markers that, in combination with antigen-specific profiling, provide a detailed picture of the adaptive immune response in Type 1 diabetes (T1D). The CD4+ T cell effector compartment (referred to as “Teff” in this article) has been extensively analyzed, particularly because the HLA genes most strongly associated with T1D are MHC class II alleles that form restriction elements for CD4+ T cell recognition. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 94 publications
1
16
0
Order By: Relevance
“…Collectively, these data suggest that immune profiles may identify candidates for such therapy, albeit validation in a larger cohort is clearly necessary. Further studies are needed to accurately determine if T cells are moving to a more anergic/senescent phenotype following ATG+G-CSF therapy, as has been observed with other T cell–targeting agents that have demonstrated clinical responses (21,22). …”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these data suggest that immune profiles may identify candidates for such therapy, albeit validation in a larger cohort is clearly necessary. Further studies are needed to accurately determine if T cells are moving to a more anergic/senescent phenotype following ATG+G-CSF therapy, as has been observed with other T cell–targeting agents that have demonstrated clinical responses (21,22). …”
Section: Discussionmentioning
confidence: 99%
“…Unregulated effector T‐cell expansion through failure in the control of regulatory T‐cell populations may in an inflammatory extracellular environment influence disease onset. Furthermore, the activation of the innate immune system through neutrophils, platelets, and complement system plays an important role in the development of the disease . Today, in addition to susceptibility loci in HLA, GWA studies have identified more than 60 loci associating with T1D mostly with small individual effect but together explaining most of the T1D heritability .…”
Section: Hla and Disease Associationsmentioning
confidence: 99%
“…Furthermore, the activation of the innate immune system through neutrophils, platelets, and complement system plays an important role in the development of the disease. 79,80 Today, in addition to susceptibility loci in HLA, GWA studies have identified more than 60 loci associating with T1D mostly with small individual effect but together explaining most of the T1D heritability. 81 Combining candidate gene results with GWA risk SNPs may soon provide a genetic risk score to identify T1D patients.…”
Section: Hla and Disease Associationsmentioning
confidence: 99%
“…38,39 Second, new immunomonitoring tools were developed to measure the ratio of effector T cells to regulatory T cells, which provided a new immune measurement to evaluate drug safety and mechanisms in future studies. 40 Third, several pharmaceutical companies and some academic centers expanded their research to develop safer versions of interleukin-2 (called interleukin-2 muteins), which are projected to have a larger margin of safety owing to selective targeting properties. 41 Fourth, the Immune Tolerance Network and Juvenile Diabetes Research Foundation established a preclinical research consortium, which developed a multicenter protocol for more robust validation testing in mice.…”
Section: Type 1 Diabetesmentioning
confidence: 99%